Enlightenment as the normative principle of social rationality - Klein, Joel T. (Studia Kantiana, 2023)
This paper argues that Kant’s philosophy entails a normative concept of social rationality distinct from other normative concepts such as moral and juridical rationality. I also argue that the normative demands of social rationality are embodied in the regulative idea of enlightenment which implies a profound intersubjective and moral character that unfolds in multiple layers and perspectives.